Clay Statues from Canosa - Kari Dodson; Violaine Jeammet (Les Carnets de l’ACoSt)
ll worthwhile to visit Canosa to get a sense of the archaeological contexts—the rock cut tombs within which the figures were found. The history of these tombs comprises a series of discoveries, losses, and rediscoveries. Most of the tombs can be visited today.